2020
DOI: 10.3389/fmolb.2020.616341
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in the Drug Development Targeting SARS-CoV-2 Main Protease as Treatment for COVID-19

Abstract: The sudden outbreak of 2019 novel coronavirus (2019-nCoV, later named SARS-CoV-2) rapidly turned into an unprecedented pandemic of coronavirus disease 2019 (COVID-19). This global healthcare emergency marked the third occurrence of a deadly coronavirus (CoV) into the human society after entering the new millennium, which overwhelmed the worldwide healthcare system and affected the global economy. However, therapeutic options for COVID-19 are still very limited. Developing drugs targeting vital proteins in vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 62 publications
(80 reference statements)
0
80
0
2
Order By: Relevance
“…Extensive studies repurposed antiviral drugs against M pro [ 19 , 46 , 47 ], (Z [ 9 ]. Abd El-Mordy et.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies repurposed antiviral drugs against M pro [ 19 , 46 , 47 ], (Z [ 9 ]. Abd El-Mordy et.…”
Section: Discussionmentioning
confidence: 99%
“…Domain III (residues 198–303) regulates 3CL pro homodimerization, which is required for enzymatic activity [ 14 ]. 3CL pro is widely regarded as an excellent target for COVID-19 drug development because it is essential for viral replication and has a cleavage specificity distinct from human cellular proteases, reducing the likelihood of off-target effects [ 13 , 15 , 16 ]. The preferred sequence at cleavage sites is LQ ↓ (S, A, G), with the arrow indicating the cleavage site [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this is the limited number of X-ray structures deposited in the Protein Data Bank (PDB) for PLpro (around 24 structures) compared to the main protease (Mpro, around 200 structures). Additionally, compared to Mpro[ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] ], fewer reports about targeting PLpro is presented in literature[ [46] , [47] , [48] , [49] , [50] , [51] , [52] ]. In the context of drug repurposing to treat COVID-19, Balasubramaniam et al [ 46 ] reported potential targeting of three SARS-CoV-2 proteins, RNA-dependent RNA polymerase, papain-like proteinase and helicase, by the antiviral drug elbasvir through virtual screening of 54 FDA-approved antivirals and 3300 investigational drugs.…”
Section: Introductionmentioning
confidence: 99%